A virtualização do trabalho na administração pública municipal - Villela, Lucila Carvalho Valladão Nogueira (2024)
This research aims to analyze the implementation of teleworking in Municipal Public Administration, especially after the COVID-19 pandemic. To meet the general objective of the research, 3 articles will be presented: the first, a bibliometric analysis, with a systematic literature review, about scientific production on teleworking during the years 2020 and 2023; the second, a documentary study, followed by a SWOT analysis, on the teleworking model adopted by the Municipality of Três Corações/MG; and, finally, based on the theoretical factors obtained in Article 1, as well as the empirical analysis carried out in Article 2, the third presents a technical report with guidelines for implementing teleworking in municipal public organizations, with a focus on performance management. From the work carried out, it was possible to observe the growth of scientific production on the subject, although there is still a gap in studies that deal with the municipal system. It was also found that the literature identifies aspects more positive points than negative points in adopting the teleworking regime, according to empirical research carried out in various sectors, public and private. From the SWOT analysis, positives and negatives of the model adopted in the Municipality of Três Corações/MG were identified, which also served as the basis for the creation of the Conclusive Technical Report. The elaboration of this work is justified, as there is a tendency towards the adoption of flexible work regimes, including in Public Administration, which is subject to Constitutional Principles that require compliance with appropriate legal procedures, and municipal managers must be guided towards the choose the correct ways to implement it. It is expected that the results of this research will contribute to the organized and regulated growth of teleworking in public organizations, by reading the Conclusive Technical Report “Tools for standardizing and implementing teleworking in Municipal Public Administration”.